Energy Consumption and Health Outcomes in Africa - (:unkn) unknown (My University, 2016)
We examine causal links between energy consumption and health indicators (Mortality rate under-5, life expectancy, greenhouse effect, and government expenditure per capita) for a sample of 16 African countries over the period 1971-2010 (according to availability of countries' data). We use the panel-data approach of Kónya (2006), which is based on SUR systems and Wald tests with country specific bootstrap critical values. Our results show that health and energy consumption are strongly linked in Africa. Unilateral causality is found from energy consumption to life expectancy and child under-5 mortality for Senegal, Morocco, Benin, DRC, Algeria, Egypt, and South Africa. At the same time, we found a bilateral causality between energy consumption and health indicators in Nigeria. In particular, our findings suggest that electricity consumption Granger causes health outcomes for several African countries.
Keywords: African Research